Does Janani Shishu Suraksha Karyakram ensure cost-free institutional delivery? A cross-sectional study in rural Bankura of West Bengal, India - Janmenjoy Mondal; Dipta Kanti Mukhopadhyay; Sujishnu Mukhopadhyay; Apurba Sinhababu (Wolters Kluwer Medknow Publications, 2015)
Background: Janani Shishu Suraksha Karyakram (JSSK) was launched in India to ensure cost-free institutional delivery. Objectives: 1) To assess the awareness of recently delivered women regarding JSSK 2) To estimate the cost of institutional delivery and its differentials. Materials and Methods: A community-based, cross-sectional study was conducted in a rural community in Bankura, West Bengal, India in 2013, among 210 women who delivered babies in the last 12 months. Information regarding sociodemographic and health service-related variables as well as item-wise costs incurred for institutional delivery were collected. Costs were expressed in Indian National Rupee (INR). A nonparametric, bivariate analysis was performed to examine the difference in median cost. Results: All components of JSSK were known to 12.9% women; the highest (77.1%) for admission and lowest (29.0%) for blood transfusion. The median (±IQR) costs of delivery in the Block level Primary Health Center (PHC), medical college, and private facilities were INR 205.0 (±825.0), 900.0 (±1013.0), and 6600.0 (±16195.0), respectively. Median cost of normal delivery in a private facility (INR 2750.0) was 3.6 times of that in a government facility (INR 765.0). Median direct cost of caesarian section (CS) in a government facility (INR 1100.0) was nearly one-fifteenth of that in a private facility (INR 16,350.0). Cash incentives under Janani Suraksha Yojana for poor and socially marginalized women could not cover the cost of CS delivery in a government facility. Conclusion: Gaps existed in the awareness of beneficiaries regarding entitlement under JSSK. Drugs and transport were two major causes of out-of-pocket (OOP) expenditure in public health facilities.